1990
DOI: 10.1007/bf01272760
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopamine D-1 and D-2 antagonists on decision making by rats: No reversal of neuroleptic-induced attenuation by scopolamine

Abstract: The effects of the dopamine (DA) D-1 antagonist SCH 23390 and the D-2 antagonists haloperidol and sulpiride on decision making in thirsty rats were investigated. The problem given to the rats was to choose between two behaviours, locomoting or lever-pressing, in order to obtain rewards (water). SCH23390 and haloperidol dose-dependently reduced the number of rewards obtained. However, only minor effects were seen on the decision making parameters. DA is thus important for initiation and/or performance of learne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
2
1
1
Order By: Relevance
“…We note that unlike other published reports [71, 72], the effects of the DA D 1 agonist/antagonist on decision making were modest at best ( Fig. S2 ), but not uncommon [7375]. In our case, the DA D 1 agonist and antagonist had a noticeable effect on motivation which was further supported with the photometric analysis of DA release in the NAc.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We note that unlike other published reports [71, 72], the effects of the DA D 1 agonist/antagonist on decision making were modest at best ( Fig. S2 ), but not uncommon [7375]. In our case, the DA D 1 agonist and antagonist had a noticeable effect on motivation which was further supported with the photometric analysis of DA release in the NAc.…”
Section: Discussionsupporting
confidence: 86%
“…We note that unlike other published reports [71,72], the effects of the DA D1 agonist/antagonist on decision making were modest at best (Fig. S2), but not uncommon [73][74][75].…”
Section: α2a Adrenoceptor Modulation Of Stress Induced Catecholamine ...contrasting
confidence: 94%
See 1 more Smart Citation
“…For the remaining rats (N = 11), decision making was assessed 10 min after administration of the selective D1 receptor antagonist SCH23390 (0.03 mg/kg; Bourne, 2001) or saline. Doses used were similar to those used in previous studies of reinforcement learning (Ljungberg and Enquist, 1990;Keeler et al, 2014) and do not produce motoric or behavioral impairments that are observed with higher doses of these drugs (Collins et al, 1991;Mattingly et al, 1993). Choice behavior following administration of sulpiride, SCH 23390, or saline was analyzed using the same reinforcementlearning algorithm described above.…”
Section: Pharmacological Studies Of Dopamine Receptorsmentioning
confidence: 99%